2017
DOI: 10.1371/journal.pone.0178792
|View full text |Cite
|
Sign up to set email alerts
|

Rotating night work, lifestyle factors, obesity and promoter methylation in BRCA1 and BRCA2 genes among nurses and midwives

Abstract: Some recent evidence suggests that environmental and lifestyle factors may modify DNA methylation. We hypothesized that rotating night work and several modifiable factors may be associated with the methylation of the promoter regions within two tumor suppressor and DNA repair genes: BRCA1 and BRCA2. The methylation status of BRCA1 and BRCA2 was determined via qMSP reactions using DNA samples derived from blood leucocytes of 347 nurses and midwives working rotating nights and 363 working during the days. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 91 publications
0
12
0
1
Order By: Relevance
“…To the best of our knowledge, no formal assessment for WBC BRCA2 methylation with respect to breast or ovarian cancer risk has been conducted. Notably, in a recent study using a low detection limit, Peplonska and colleagues detected evidence of WBC BRCA2 and BRCA1 methylation in 18.3% and 21.5%, respectively, among (presumably) cancer-free participants [134]. However, their estimates are unusually high, also for BRCA1 methylation.…”
Section: Normal Tissue Brca1/2 Methylation and Risk Of Breast And Ovamentioning
confidence: 99%
“…To the best of our knowledge, no formal assessment for WBC BRCA2 methylation with respect to breast or ovarian cancer risk has been conducted. Notably, in a recent study using a low detection limit, Peplonska and colleagues detected evidence of WBC BRCA2 and BRCA1 methylation in 18.3% and 21.5%, respectively, among (presumably) cancer-free participants [134]. However, their estimates are unusually high, also for BRCA1 methylation.…”
Section: Normal Tissue Brca1/2 Methylation and Risk Of Breast And Ovamentioning
confidence: 99%
“…Furthermore, some studies indicate that the cancer risk of BRCA1 and BRCA2 mutation carriers might be reduced by a healthy lifestyle (e.g. no smoking, physical activity) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Douglas (2014), and Wickremaratne et al (2017) found in their study that there was no significant association between colorectal cancer and shift work of nurses and midwives, Shi et al (2020) and Lieberman et al (2020), on the contrary, found in their research that the risk of cancer and colorectal cancer is higher for nurses who work night shifts, especially for those who do such work for a long time. Peplonska et al (2017) notes that the study did not show an association between night shift work and tumor markers for breast and ovarian cancer. Trossman (2015) however, writes that in some states of America nurses are encouraged to go to rest or fall asleep briefly during night work, not to struggle with their circadian rhythm and not to disturb the biological clock, to be able to plan their own schedule, train attention, recognize fatigue, control sleep, and have education on balancing work and private life.…”
Section: Methodsmentioning
confidence: 75%